Respostas
respondido por:
10
-2x² + 6x = 0
x.(-2x + 6) = 0
x = 0
ou...
-2x + 6 = 0
-2x = -6
x = 6/2
x = 3
x.(-2x + 6) = 0
x = 0
ou...
-2x + 6 = 0
-2x = -6
x = 6/2
x = 3
HeitorSamuel:
Muito Obrigado '-'
respondido por:
5
Resolução:
-2x²+6x=0 (-1) -- Multiplicando por -1
2x² - 6x = 0
2x( x - 3) =0
x = 0 -- Resposta
x - 3 = 0
x = 3 -- Resposta
-2x²+6x=0 (-1) -- Multiplicando por -1
2x² - 6x = 0
2x( x - 3) =0
x = 0 -- Resposta
x - 3 = 0
x = 3 -- Resposta
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás